Battery management system employing passive control method - Fahmi, Muhamad Aqil Muqri Muhamad; Yusoff, Siti Hajar; Gunawan, Teddy Surya; Zabidi, Suriza Ahmad; Abu Hanifah, Mohd Shahrin (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
A battery management system (BMS) is essential for maintaining peak efficiency and longevity of rechargeable batteries. Conventional battery management system techniques often struggle to monitor, protect, and particularly have difficulties in balancing batteries. The project proposed has introduced a battery management system that employs passive control techniques to address excess energy and overcome these challenges. In the proposed design, a shunt resistor dissipates surplus energy from lithium-ion battery cells into heat following the proposed BMS design. This passive control technique is economically efficient, uncomplicated, and does not require an external power source. A prototype of the proposed BMS design was tested and was able to accurately monitor the battery, dissipate excess energy, and protect the battery while maintaining the cell charge balance. These findings suggest that the proposed BMS has the potential to improve both the effectiveness and longevity of rechargeable batteries.